Onchocerciasis (River Blindness) 1: the parasite, vector, disease and treatment - Hopkins, MBE, Adrian (Henry Stewart Talks, 2020)
What is Onchocerciasis and its impact, The Life cycle of the disease, The vector, The parasite, The disease in the eye, skin, and brain, Principles of treatment and breaking the transmission cycle including use of ivermectin